Use of recombinant antigen in the diagnosis of Crimean-Congo haemorrhagic fever virus infection - Seleka, G. P. (My University, 2001)
The Special Pathogens Unit (SPU) of the National Institute for Virology has diagnosed a total of 158 cases of Crimean-Congo haemorrhagic fever (CCHF) from the time that the disease was first recognized in South Africa in 1981 up until the end of 2000. The virus has a propensity to cause nosocomial infections, and consequently rapid diagnosis is important for the isolation of the patient and the institution of barrier-nursing to protect medical staff and the community at large. Thus it is essential that the SPU should have the latest diagnostic and research tools available. Diagnosis of CCHF is generally confirmed by isolation of the virus, detection of viral RNA amplified by reverse transcriptase polymerase chain reaction (RT-PCR), demonstration of seroconversion or a >4-fold increase in IgG antibody titre, or detection of specific IgM antibody activity. Virus can be isolated in 1-6 days in cell culture, but the method is less sensitive for the isolation of low concentrations of virus than the use of suckling mice which, however, takes 7-9 days.
A dissertation submitted to the Faculty of Health Sciences University of the Witwatersrand, Johannesburg for the degree of Master of Science.
Keywords: Hemorrhagic Fever Virus, Crimean-Congo; Antigens